ALTERNATIF MENINGKATKAN PEMAHAMAN SISWA MATERI KETENAGAKERJAAN MASA PANDEMI COVID-19 MELALUI MODEL SESI INTEGRASI BERBASIS CLASSROOM, - Ruminten Supadmi (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2022)
The classroom-based “Integration Session” model is used in this study as an alternative learning for the Covid-19 pandemic disaster preparedness. The type of research is Classroom Action Research with 2 cycles. Two meetings in each cycle. Research subjects, students of class XI IPS 2 SMA Negeri 1 Rangkasbitung FY 2021/2022. Tests and non-tests were used as instruments. Data collection techniques through 1). Documentation: Google Classroom application, Google Form, Google Documentation, 2) Essays and multiple choice tests, 3) To find out student responses to the application of the classroom-based “Integration Session” model, a questionnaire was used. Data reduction, data presentation, and drawing conclusions were used as analytical steps. Before applying the "Integration Session" model, the average score was 74,33 categorized as "Good". The learning outcomes after applying the Integration Session model obtained the "Very Good" category with an average of 83.15 categorized as "Very Good", which is the result of research on the application of the classroom-based "Integration Session" model, as an alternative to learning for the Covid-19 pandemic disaster preparedness. Presentation value 86, 78. The results of cycles 1 to 2 increased 1.16%. The effect of applying the "Integration Session" model has increased by 10,02%, this means that the Integration Session model is very influential in learning. Meanwhile, the category "Good". because students agree that the classroom-based Integration Session model is applied during the Covid-19 pandemic with a questionnaire result of 63.75